DETECTION OF Leishmania (Viannia) IN Nyssomyia neivai AND Nyssomyia whitmani BY MULTIPLEX POLYMERASE CHAIN REACTION, IN SOUTHERN BRAZIL - Neitzke-Abreu, Herintha Coeto; Reinhold-Castro, Kárin Rosi; Venazzi, Mateus Sabaini; Scodro, Regiane Bertin de Lima; Dias, Alessandra de Cassia; Silveira, Thaís Gomes Verzignassi; Teodoro, Ueslei; Lonardoni, Maria Valdrinez Campana (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
Sandflies transmit pathogens of leishmaniasis. The natural infection of sandflies by Leishmania (Viannia) was assessed in municipalities, in the state of Paraná, in Southern Brazil. Sandflies were collected with Falcão and Shannon traps. After dissection in search of flagellates in digestive tubes and identification of the species, female sandflies were submitted to the Multiplex Polymerase Chain Reaction (multiplex PCR) for detection of the fragment of the kDNA of Leishmania (Viannia) and the fragment from the IVS6 cacophony gene region of the phlebotomine insects. The analysis was performed in pools containing seven to 12 guts from females of the same species. A total of 510 female sandflies were analyzed, including nine Migonemyia migonei, 17 Pintomyia fischeri, 216 Nyssomyia neivai, and 268 Nyssomyia whitmani. Although none of the females was found naturally infected by flagellates through dissection, the fragment of DNA from Leishmania (Viannia) was shown by multiplex PCR in one sample of Ny. neivai (0.46%) and three samples of Ny. whitmani (1.12%). It was concluded that Ny. neivai and Ny. whitmani are susceptible to Leishmania infection, and that multiplex PCR can be used in epidemiological studies to detect the natural infection of the sandfly vector, because of its sensitivity, specificity and feasibility.